Mid-Holocene East Asian summer monsoon and vegetation changes recorded by a stalagmite from Huangjin Cave, northern China - Bin Zhao; Yongjin Wang; Liang Ning; Qingfeng Shao; R. Lawrence Edwards; Yijia Liang; Kan Zhao (Quaternary Science Reviews, 2026)

Heterogeneous responses of the East Asian summer monsoon and hydroclimate in southwest China to Bond events during the Late Holocene - Bin Zhao; Tianxiang Fu; Zhigang Zhang; Kan Zhao; Zhenqiu Zhang; Qingfeng Shao; Yijia Liang; Yongjin Wang (Global and Planetary Change, 2026)

Salt-activated bimetal–phenolic nanoadhesive for broad-spectrum micro- and nanoplastic removal across salinity gradients - Zheng Cai; Qingfeng Yao; Lan Zhao; Yan Cao; Yishuang Li; Xianluo Hu; Jingming Gong (Chemical Engineering Journal, 2026)

Low-lethal and intergenerational effects of broflanilide on the diamondback moth, Plutella xylostella (L.) - Kunkun Wang; Qiqi Zhao; Chenyao Yang; Chen Shen; Qichao Zhang; Renwen Zheng; Pei Liang; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2026)

Plastic mulching and crop type govern the vertical distribution and composition of microplastics in a major agricultural irrigation system - Xuezheng Yu; Weiying Feng; Liu Wang; Yuxin Deng; Chia Min Ho; Yunping Han; Qingfeng Miao; Meng Zhao; José Manuel Gonçalves; Sundaravelpandian Kalaipandian (Environmental Research, 2026)

Experimental investigation of a residential multi-split air-conditioning system with partial heat recovery for domestic hot water - Yujue Zhou; Baolong Wang; Wenxing Shi; Zhigang Wang; Qingfeng Bie; Xianguo Jiang; Zhanwen Zhao (Energy and Buildings, 2026)

Combined effects of Chlorella application and reduced nitrogen fertilization on nitrogen use efficiency and crop yield in facility vegetable systems - Guoliang Zhao; Jingyu Sun; Xingcheng Hu; Zhengxi Cai; Chen Li; Qingfeng Chen (Applied Soil Ecology, 2026)

Spatial and temporal evolution of the groundwater depth and indirect effects during the spring irrigation period in the Hetao Irrigation District - Yi Zhao; Haibin Shi; Xianyue Li; Shuya Yang; Haoqi Han; Yunlei Dong; Qingfeng Miao; Jianwen Yan; Cong Hou; Xu Dou (Irrigation Science, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Exploring the polymorphism of foxtail millet proteins and the mechanisms of activity variations driven by varietal differences - Zeyu Peng; Jia Cao; Hongyue Zhao; Bowen Yang; Jianjun Cheng; Qingfeng Ban (Food Research International, 2026)

Variations in soil nutrients and functional microbe abundances govern GHGs emissions under different rice rotation regimes - Zheng Zhao; Xiangyang Gui; Jinxi He; Zhimin Sha; Qingfeng Wang; Deping Zhou; Changbin Chu; Shuhang Wu (Agricultural Systems, 2026)

Contrasting response of the Asian Summer monsoon to bipolar climates and implications for ice core chronology during Marine Isotope Stages 5c-a inferred from stalagmite record, Central China - Zhenjun Wang; Shitao Chen; Yongjin Wang; Yalan Zeng; Li Wu; Yijia Liang; Gongzhe Chen; Zhenqiu Zhang; Shaohua Yang; Chunsheng Hu; Peng Sun; Qingfeng Shao; et al. (Global and Planetary Change, 2026)

Inferring irrigation regimes and sunshine duration from the distribution and spectral characteristics of farmland microplastics - Hangzheng Zhao; Xu Han; Changming Cao; Ziyi Zan; Bo-Tao Zhang; Jiamin Wang; Qingfeng Tang; Weifeng Yue; Yan Liu (Environmental Pollution, 2026)

Optimization of fertilization regimes for major crops in the Hetao Irrigation District based on the DNDC model and evaluation of economic benefits - Cong Hou; Haibin Shi; Yan Yan; Qingfeng Miao; Yi Zhao; Sihan Xue; Jiapeng Zhang; Weiping Li (European Journal of Agronomy, 2026)

Ethyl ferulate attenuates allergic asthma via inhibiting macrophage M2 polarization through STAT6/IRF4 pathway - Longlong Ge; Weizhen Chen; Shuguang Han; Huan Yang; Mingchen Du; Shengpeng Li; Xinran Bai; Peilin Zhao; Dan Chen; Qingfeng Pang; Yaxian Wu (Inflammation Research, 2026)

Seep-related carbonates on continental shelves: Distinctive processes and morphologies revealed by the Qiongdongnan Shelf, South China Sea - Hongli Wang; Qiang Zhao; Fangqi Wang; Qingfeng Hua; Qiuhong Xie; Yangting Liu; Chenguang Liu; Yanliang Pei; Xishuang Li; Yikai Feng; Fei Cao (Marine Geology, 2026)

Effect of critical atomizing-flow distributor on thermal–hydraulic performance of finned evaporator - Zhili Sun; Jinjin Wang; Qifan Wang; Guanyuan Su; Qingfeng Bie; Yue Zhao; Jinfeng Chen; Hongyu Zhao; Zhan Wang; Xiaoyu Liu; Yihan Liu; Wenfu Zhang; et al. (International Journal of Refrigeration, 2026)

Exosomal Protein Biomarkers for Predicting Early Neurological Deterioration Following Intravenous Thrombolysis in Acute Ischemic Stroke - Jiamin Li; Zixin Wang; Yingnan Zhou; Xinyi Wang; Qi Kong; Jiameng Li; Boyi Yuan; Yun Chen; Wan Wang; Jiapeng Zhao; Jinming Sheng; Haiping Zhao; et al. (Translational Stroke Research, 2026)

Mitochondria–membrane contact duration: a spatial checkpoint for oxidative cell death - Qingfeng Wu; Qingbin Zhao (Apoptosis, 2026)

The effects of endophytic fungal metabolites from Conyza blinii on antioxidant capacity and healthspan in Caenorhabditis elegans - Yixuan Qi; Yujie Jia; Yixin Chen; Hongying Zhu; Yirong Xiao; Zhao Chen; Limin Su; Xinyu Zhang; Wenrong Zhao; Zhengjiang Li; Youpeng Tuo; Tongliang Bu; et al. (Natural Product Research, 2026)

Regular and mechanism of millennial scale weak monsoon events during the late MIS7 to early MIS6.5 period - Shaohua Yang; Shitao Chen; Yongjin Wang; Bin Zhao; Yijia Liang; Zhenjun Wang; Zhenqiu Zhang; Quan Wang; Qingfeng Shao; Lei Lu; Chuan-Chou Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Asynchronous abrupt changes of lake ecosystems in the Anthropocene - Dinggui Wu; Tian Xia; Qingfeng Zhao; Yibin Sun; Na Song; Man Li; Tianchen He (Global and Planetary Change, 2026)

Early Holocene monsoon abrupt changes and hydrological response as recorded by a multi-proxy stalagmite from Yuquan Cave, Central China - Xiaomeng Cui; Junji Zhu; Kan Zhao; Jiangying Wu; Yijia Liang; Liang Ning; Qingfeng Shao; Yongjin Wang (Science China Earth Sciences, 2026)

Effects of anthropogenic activities on soil microbial communities and greenhouse gas fluxes in coastal wetlands of the Yellow River Delta, China - Jingyu Sun; Xiaoya Xu; Zihao Wang; Kun Li; Chenmiao Liu; Chen Li; Zhengxi Cai; Xinkun Zhao; Xinyi Xu; Hongjie Di; Qingfeng Chen (Journal of Environmental Sciences, 2026)

Evolution of Asian summer monsoon and vegetation in southwestern China and their linkages with wildfire history during the Holocene - Bin Zhao; Yijia Liang; Yongjin Wang; Kan Zhao; Qingfeng Shao; Hai Cheng (Global and Planetary Change, 2026)

Progestins as emerging contaminants in soil: An investigation on their pollution characteristics and ecological risks - Qianwen Jiao; Zhenzhen Xu; Yuzhen Liu; Yimin Li; Yifan Zhao; Qingfeng Chen; Xiaoyan Shen (Environmental Research, 2026)

The tripartite 4.2 ka event in East Asia: Stalagmite evidence and its interregional implications - Zhenqiu Zhang; Weihong Zhang; Zhiyuan Shang; Jianshun Chen; Yijia Liang; Qingfeng Shao; Kan Zhao; Yongqiu Wu; Yongjin Wang (Global and Planetary Change, 2026)

Underlying mechanism and the effect of diacylglycerols on the protein structural stability and in vitro digestibility of pork meatballs - Xinxin Zhao; Yunling Jiang; Zixin Luo; Xiankun Sun; Jiangyu Zhu; Hai Yu; Xinyan Peng; Qingfeng Ge (Food Chemistry, 2026)

Sulfonamides and their transformation products in the Yellow River Delta, China: Occurrences, source apportionment, and ecological risks - Yimin Li; Qianwen Jiao; Yifan Zhao; Qingyue Xiang; Hongping Wang; Zhenzhen Xu; Qingfeng Chen; Xiaoyan Shen (Environmental Pollution, 2026)

Diffusion of micron-sized oil droplets accompanying short-term thermal airflow with weak buoyancy in machining intervals - Yuming Zhang; Yang Yang; Yi Wang; Jia-ning Fan; Tongtong Zhao; Jun Gao; Qingfeng Cao; Ningbin Zhu; Yong Cui (Building and Environment, 2026)

Disentangling ENSO- and ITCZ-related hydroclimate signals from replicated stalagmite multiproxy over the past 2500 years - Kui Gao; Tanui Moses Kipkorir; Kan Zhao; Xiuyang Jiang; Jingwei Zhang; Qihang Zhang; Junji Zhu; Sixian Wang; Yongjin Wang; Zhenqiu Zhang; Qingfeng Shao; R. Lawrence Edwards; et al. (Global and Planetary Change, 2026)

Preliminary application of synchrotron time-resolved SAXS in in-situ study of dust explosion - Haijuan Wu; Jiahao Liu; Xiaolan Ji; Wenmin Li; Longlong Yang; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Xiong Cao; Yixin Zhao (Fuel, 2026)

Anammox enhanced anoxic/oxic/oxic/anoxic process for removing carbon, nitrogen, and phosphorus from extremely low carbon/nitrogen ratio wastewater: Feasibility, performance and mechanism - Qingfeng Cheng; Yutong Chen; Wenxing Zhao; Xujing Guo; Lichao Nengzi; Zhongyou Gong; Erdeng Du; Mingguo Peng (Bioresource Technology, 2026)

Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.

Cover Image - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
The cover image is based on the article Macro‐Hybrid and Micro‐Hybrid of Fish by Shaojun Liu et al., https://doi.org/10.1111/raq.70106 . image

Intensification of Weddell Sea deep water in the southern Scotia Sea since ∼0.4 Ma: Mechanistic links to the mid-Brunhes transition - Qiang Zhao; Hongli Wang; Yanpeng Zheng; Kai Liu; Xishuang Li; Chenguang Liu; Yanliang Pei; Qingfeng Hua; Long Ma; Yonghua Wu; Shulan Ge; Fei Cao; et al. (Quaternary Science Reviews, 2025)

The 9.2 ka event during the early Holocene recorded by a stalagmite from Dongge Cave - Chuntong He; Bin Zhao; Yongjin Wang; Kan Zhao; Shaohua Yang; Qingfeng Shao; Hai Cheng; Yijia Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Double-plunging structure of the Bond 4 event evidenced in new mid-Holocene stalagmite records from northern China - Quan Wang; Yingfang Cui; Kan Zhao; Jianshun Chen; Qingfeng Shao; Jianghu Lan; Liangcheng Tan; Lei Ding; Hongan Dong; Lili Dai; Yongjin Wang (Global and Planetary Change, 2025)

Chinese speleothem evidence of the early-mid Holocene transition and the instability of Asian summer monsoon - Bin Zhao; Yongjin Wang; Kan Zhao; Jianjun Yin; Quan Wang; Shaohua Yang; Qingfeng Shao; Hai Cheng; Yijia Liang (Global and Planetary Change, 2025)

The impact of milling degrees on rice quality using simultaneous rheology and FTIR techniques: Focus on starch structure - Weijie Qi; Yaxing Xie; Hongyue Zhao; Jianjun Cheng; Qingfeng Ban; Mingruo Guo (Food Chemistry, 2025)

Centennial- to multidecadal-scale monsoon precipitation variability during the mid-Holocene - Yifei Wang; Zhenqiu Zhang; Yongjin Wang; Kan Zhao; Yijia Liang; Kui Gao; Jianshun Chen; Qingfeng Shao; Zeji Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Hydroclimate changes in southwestern China from Dark Age Cold Period to Medieval Climate Anomaly and their global teleconnections - Bin Zhao; Kan Zhao; Yaoqi He; Yongjin Wang; Qingfeng Shao; Hai Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

In situ study of the effect of ignition delay time on the lignite dust explosion using synchrotron radiation time-resolved SAXS - Xiaolan Ji; Jiahao Liu; Haijuan Wu; Longlong Yang; Wenmin Li; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Lili Dong; Yuanyang Wang; Yixin Zhao; Xiong Cao; et al. (Fuel, 2025)

Performance and mechanism of synchronous carbon and nitrogen removal from secondary effluent by denitrification coupled with partial-denitrification anammox - Qingfeng Cheng; Yanting Tu; Wenxing Zhao; Lichao Nengzi; Zhongyou Gong; Erdeng Du; Mingguo Peng (Journal of Cleaner Production, 2025)

Multi-factor analysis of enzyme activities under anthropogenic influence in the coastal wetland of the Yellow River Delta, China - Jingyu Sun; Xiaoya Xu; Xinkun Zhao; Qingfeng Chen (Journal of Environmental Management, 2025)

Persistently centennial to millennial variability of Asian summer monsoon and north-south coupling during the late penultimate glacial period - Wei Huang; Zhenqiu Zhang; Kan Zhao; Yongjin Wang; Qingfeng Shao; Jinguo Dong; Xiuyang Jiang; Xiumin Zhai; Carlos Pérez-Mejías (Global and Planetary Change, 2025)

Occurrence, distribution, and potential risk of 61 glucocorticoids in soils in Shandong Province, China - Qianwen Jiao; Yifan Zhao; Yimin Li; Yuzhen Liu; Hongping Wang; Zhenzhen Xu; Qingfeng Chen; Xiaoyan Shen (Environmental Pollution, 2025)

Physiological and transcriptomic responses of fall armyworm, Spodoptera frugiperda to host-plant switching - Jun Peng; Renwen Zheng; Jinyuan Zhao; Jinhui Zhang; Qianqian Li; Dongyan Huang; Xin Zhou; Lijuan Liu; Zhuocong Li; Xiaoman Ning; Sihan Lu; Qingfeng Tang (Journal of Pest Science, 2025)

Effects of conservation agriculture on carbon dynamics across eroded slopes: A global synthesis - Liangang Xiao; Kebing Zhao; Yudi Wang; Rongqin Zhao; Zhixiang Xie; Qingfeng Hu (Agriculture, Ecosystems & Environment, 2025)

Mechanisms of plant-derived and microbial residue carbon in coastal wetland soils in response to salinity gradients - Xinkun Zhao; Jingyu Sun; Chenmiao Liu; Enyue Zhang; Guoliang Zhao; Qingfeng Chen (CATENA, 2025)

Vibration damping and finite element analysis of a 10 MW jacket-type offshore wind turbine - Jigang Zhang; Haodong Sui; Zhehao Ma; Wenli Chen; Qingfeng Yan; Wei Li; Hongjian Xu; Fengbo Yu; Yun Niu; Junxian Zhao (Ocean Engineering, 2025)

An occupational health assessment of dinotefuran exposure in greenhouse vegetable workers: Metabolomic profiling and toxicokinetic analysis - Jiamin Li; Hao Zhang; Ke Zhao; Chengcheng Han; Changjian Li; Lei Fang; Haiyong Jia; Yong Wang; Hanqiu Tang; Qingfeng Zhai; Peng Xue (Journal of Hazardous Materials, 2025)

HMGB1: A New Target for Ischemic Stroke and Hemorrhagic Transformation - Jiamin Li; Zixin Wang; Jiameng Li; Haiping Zhao; Qingfeng Ma (Translational Stroke Research, 2025)
Stroke in China is distinguished by its high rates of morbidity, recurrence, disability, and mortality. The ultra-early administration of rtPA is essential for restoring perfusion in acute ischemic stroke, though it concurrently elevates the risk of hemorrhagic transformation. High-mobility group box 1 (HMGB1) emerges as a pivotal player in neuroinflammation after brain ischemia and ischemia–reperfusion. Released passively by necrotic cells and actively secreted, including direct secretion of HMGB1 into the extracellular space and packaging of HMGB1 into intracellular vesicles by immune cells, glial cells, platelets, and endothelial cells, HMGB1 represents a prototypical damage-associated molecular pattern (DAMP). It is intricately involved in the pathogenesis of atherosclerosis, thromboembolism, and detrimental inflammation during the early phases of ischemic stroke. Moreover, HMGB1 significantly contributes to neurovascular remodeling and functional recovery in later stages. Significantly, HMGB1 mediates hemorrhagic transformation by facilitating neuroinflammation, directly compromising the integrity of the blood–brain barrier, and enhancing MMP9 secretion through its interaction with rtPA. As a systemic inflammatory factor, HMGB1 is also implicated in post-stroke depression and an elevated risk of stroke-associated pneumonia. The role of HMGB1 extends to influencing the pathogenesis of ischemia by polarizing various subtypes of immune and glial cells. This includes mediating excitotoxicity due to excitatory amino acids, autophagy, MMP9 release, NET formation, and autocrine trophic pathways. Given its multifaceted role, HMGB1 is recognized as a crucial therapeutic target and prognostic marker for ischemic stroke and hemorrhagic transformation. In this review, we summarize the structure and redox properties, secretion and pathways, regulation of immune cell activity, the role of pathophysiological mechanisms in stroke, and hemorrhage transformation for HMGB1, which will pave the way for developing new neuroprotective drugs, reduction of post-stroke neuroinflammation, and expansion of thrombolysis time window.

Gut bacteria of the fall armyworm, Spodoptera frugiperda, promote host resistance against the toxic effects of lufenuron - Qianqian Li; Renwen Zheng; Jinyuan Zhao; Sihan Lu; Yue Liu; Dongyan Huang; Jinhui Zhang; Lijuan Liu; Xin Zhou; Qingfeng Tang (Journal of Pest Science, 2025)

Optimizing landslide susceptibility mapping using integrated forest by penalizing attributes model with ensemble algorithms - Wei Chen; Chao Wang; Xia Zhao; Li Bai; Qingfeng He; Xi Chen; Qifei Zhao; Ruixin Zhao; Tao Li; Paraskevas Tsangaratos; Ioanna Ilia (Earth Science Informatics, 2025)

Mechanistic model for the cotransport of colloids and radionuclides in saturated porous systems based on the interaction forces between colloids - Qi Tan; Qingfeng Tang; Xinyi Shi; Hongjie Zhao; Shuyang Li; Yuan Chen; Xiaoyan Wei; Zhen Xu; Duoqiang Pan; Wangsuo Wu (Applied Geochemistry, 2025)

Identifying low-to-middle-income residents’ secondary activity patterns using smart card data - Ziyan Zhao; Meihan Jin; Mei-Po Kawn; Qingfeng Zhou; Yongxi Gong; Yu Liu (Travel Behaviour and Society, 2025)

Characterization of flavor profiles of water-boiled pork meatballs at different ultrasonic powers using solid-phase microextraction gas chromatography–mass spectrometry combined with electronic nose - Xinxin Zhao; Bangcheng Lai; Yunling Jiang; Xiankun Sun; Zixin Luo; Qingfeng Ge; Jiaxin Chen; Hai Yu (Meat Science, 2025)

Variations of Asian summer monsoon and regional hydroclimate between the MIS 7.1 and 6.5 - Xiumin Zhai; Jingwei Zhang; Yi Li; Yijia Liang; Kan Zhao; Qingfeng Shao; Yongjin Wang; Xinggong Kong (Global and Planetary Change, 2025)

Explosion suppressing effects of Mg(OH)2/NH4H2PO4 compound powders on the methane explosion and its microscopic mechanism about capturing intermediate products - Qiuhong Wang; Leilei Zhu; Jun Deng; Qingfeng Wang; Jing Han; Dong Zhao; Youjie Sheng; Ting Pan; Jianxiong Liu (Fuel, 2025)

Biosurfactants are green and versatile enhancers for sustainable treatment of oily sludge: A review - Feng Zhao; Qingfeng Cui; Han Su; Chunyan Li; Mei Dong (Journal of Environmental Chemical Engineering, 2025)

Enhancement of calcium alginate and urea in gel-modified dry water inhibition of methane-air explosion - Qiuhong Wang; Bin Peng; Jun Deng; Wei Gao; Chao Ma; Qingfeng Wang; Youjie Sheng; Dong Zhao (Process Safety and Environmental Protection, 2025)

El Niño-Southern Oscillation signals imprinted in stalagmite δ18O from 2005 to 2017 - Jianshun Chen; Yijia Liang; Kan Zhao; Yongjin Wang; Zhenqiu Zhang; Fucai Duan; Jingwei Zhang; Qingfeng Shao; Junji Zhu; Shaohua Yang; Lian Tang; Yuqing Wang; et al. (Quaternary International, 2025)

The Research Advances in Distant Hybridization and Gynogenesis in Fish - Qizhi Liu; Shi Wang; Chenchen Tang; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Kaikun Luo; Chang Wu; Fangzhou Hu; Yude Wang; Qingfeng Liu; et al. (Reviews in Aquaculture, 2025)
Distant hybridization and gynogenesis are two prevalent breeding techniques for fishes. Drawing from the research achievements of our team and the existing literature, we summarize the reproductive traits and genetic features of fishes derived from distant hybridizations and gynogenesis, and we deduce the fundamental mechanisms of these two methods and compare them, discerning their common and different characteristics. Both distant hybridization and gynogenesis techniques can alter genotypes and phenotypes, thus establishing them as significant breeding methods. Additionally, the genetic principles and the basic biological characteristics of distant hybridization and gynogenesis in fish have been inferred. We propose the concepts of macro‐hybrid and micro‐hybrid based on extensive experimental findings from fish distant hybridizations and gynogenesis. The term “macro‐hybrid” refers to offspring from distant hybridization that possess two distinct subgenomes, each inherited from one of the two parental species, such as allodiploid and allotetraploid lineages. The concept of “micro‐hybrid” refers to offspring, including autodiploid and autotetraploid lineages, as well as those resulting from artificial gynogenesis, whose genome almost originates solely from the maternal parent but in which certain DNA fragments derived from the paternal parent insert. Distant hybridization and gynogenesis are vital techniques in fish genetics, breeding, and evolution. We highlight the prospective paths for research and application of distant hybridization and gynogenesis in fishes.

Occurrences, source apportionment, and potential risks of 55 progestins in surface water of the Yellow River Delta, China - Xiaoyan Shen; Qudi Zhang; Qingyue Xiang; Jiajun Zhao; Yue Cao; Kun Li; Jiayu Song; Zihao Wang; Xinkun Zhao; Qingfeng Chen (Journal of Hazardous Materials, 2024)

Spatial-temporal characteristics of port infrastructures on sulfur-oxide concentrations of coastal port in China - Lang Xu; Jiyuan Wu; Qingfeng Zhao; Jihong Chen; Jutong Liu; Fangren Gao; Xiaorui Liu; Jianghao Xu (Ocean & Coastal Management, 2024)

Innovation of the global international ship registry system: Evolution process and future reforms - Jihong Chen; Jianghao Xu; Qingfeng Zhao; Zeng Yuan; Li Li; Huangziyi Chen; Yinuo Liu; Yuan Xiang (Ocean & Coastal Management, 2024)

Spatial and temporal heterogeneity of soil salinity and ionic coupling relationship under the water-saving renovation of a typical irrigation district in arid and semi-arid areas - Shuya Yang; Qingfeng Miao; Haibin Shi; Yi Zhao; Xiaoyu Liu; Xin Nie; Weiying Feng; José Manuel Gonçalves; Tao Zhang; Yuxin Li; Yuli Luo (Science of The Total Environment, 2024)

Unlocking maize yield potential through exploring canopy-root interactions with nature-based nutrient management - Yupeng Zhu; Junhao Wang; Yongjun Zhu; Han Lai; Ziren Qu; Jian Zhao; Dan Wei; Pu Wang; Qingfeng Meng (Field Crops Research, 2024)

Mechanism of Self-Assembled Celastrol-Erianin Nanomedicine for treatment of breast cancer - Jiahang Tian; Kun Chen; Qian Zhang; Chong Qiu; Haibo Tong; Jingnan Huang; Mingjing Hao; Junhui Chen; Wentong Zhao; Yin-Kwan Wong; Lei Gao; Piao Luo; et al. (Chemical Engineering Journal, 2024)

Coupling low phosphorus fertilization with straw amendment highlights large crop productivity and reduced N2O emission in vegetable production - Zheng Zhao; Shuhang Wu; Haitao Zhu; Deping Zhou; Changbin Chu; Qingfeng Wang; Sixin Xu; Shumei Cai; Deshan Zhang (Applied Soil Ecology, 2024)

Microtopographic response of tilled loess slopes during stages of water erosion development - Wenli Rao; Qingfeng Zhang; Zhenyu Qian; Jincheng Liu; Guoqing Zhao (CATENA, 2024)

Insighting the effect of lard-based diacylglycerol on the thermal gelation and rheological properties of myofibrillar protein influenced by soy protein isolate - Xinxin Zhao; Xiankun Sun; Bangcheng Lai; Mangang Wu; Qingfeng Ge; Xinyan Peng; Baohua Kong; Hai Yu (Food Hydrocolloids, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Orbital- and millennial-scale hydroclimate changes in central China during the last glacial period - Quan Wang; Kan Zhao; Yongjin Wang; Jianshun Chen; Yijia Liang; Yingfang Cui; Qingfeng Shao; Xiumin Zhai; Zhenqiu Zhang; Xinggong Kong; Hai Cheng; R. Lawrence Edwards; et al. (Quaternary Science Reviews, 2024)

Multiple Matching Attenuation Based on Curvelet Domain Extended Filtering - Qingfeng Hua; Zhang Chen; Huili He; Jun Tan; Haifeng Chen; Guanbao Li; Peng Song; Bo Zhao; Xiuping Jiang (Journal of Ocean University of China, 2024)

Global daily mask use estimation in the pandemic and its post environmental health risks: Analysis based on a validated dynamic mathematical model - Ying Zhang; Fei Jiang; Fengmin Li; Shaoyong Lu; Zihao Liu; Yuwen Wang; Yiming Chi; Chenchen Jiang; Ling Zhang; Qingfeng Chen; Zhipeng He; Xiaoli Zhao; et al. (Journal of Hazardous Materials, 2024)

A study of different agricultural practices over a dozen years: Influence on soil CO2 fixation rates and soil autotrophic microbial communities - Qingfeng Wang; Changbin Chu; Zheng Zhao; Deping Zhou; Shuhang Wu (Soil and Tillage Research, 2024)

Middle to late Holocene hydroclimate variability revealed by multi-proxy stalagmite records from Jinfo Cave, central-west China - Xiumin Zhai; Jingwei Zhang; Xinmiao Chen; Jianshun Chen; Kui Gao; Yijia Liang; Qingfeng Shao; Yongjin Wang; Xinggong Kong; Kan Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Esterified wheat bran: Physicochemical properties, structure and quality improvement of Chinese steamed bread during refrigerated storage - Hua Li; Qingfeng Wu; Yanyan Guo; Ya Dai; Yali Ping; Zhenzhen Chen; Beibei Zhao (Food Chemistry, 2024)

Grafting small organic molecules on donor-acceptor polymers to regulate electron push-pull interactions for efficient H2O2 production - Shuang Zhao; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu; Dongyun Chen (Chemical Engineering Journal, 2024)

Can high-yielding maize system decrease greenhouse gas emissions largely while simultaneously enhancing economic and ecosystem benefits through the “Rhizobiont” concept? Evidence from field - Yupeng Zhu; Ziren Qu; Jian Zhao; Junhao Wang; Dan Wei; Qingfeng Meng (Science of The Total Environment, 2024)

Quantification of allochthonous and autochthonous organic carbon in large and shallow Lake Wuliangsu based on distribution patterns and δ13C signatures of n-alkanes - Qingfeng Zhao; Aifeng Zhou; Yuxin He (Organic Geochemistry, 2024)

Sources and implications of hydroxylated isoprenoid GDGTs on the northwest shelf of Australia through the Pliocene-Pleistocene era - Yuxin He; Qingfeng Zhao; Huanye Wang (Chemical Geology, 2024)

Using low-protein diet in egg production for win-win of productivity and environmental benefits should be prudent: Evidence from pilot test - Meiling Liu; Shunju Geng; Qingfeng Wang; Jinqiu Mi; Lihong Zhao; Jianyun Zhang; Cheng Ji; Hongliang Wang; Qiugang Ma; Shimeng Huang (Science of The Total Environment, 2024)

Effects of ultrasound-assisted cooking on the physicochemical properties and microstructure of pork meatballs - Xinxin Zhao; Xiankun Sun; Bangcheng Lai; Rui Liu; Mangang Wu; Qingfeng Ge; Hai Yu (Meat Science, 2024)

Occurrence, distribution, and environmental risk of 61 glucocorticoids in surface water of the Yellow River Delta, China - Qingyue Xiang; Xiaoyan Shen; Kun Li; Zihao Wang; Xinkun Zhao; Qingfeng Chen (Science of The Total Environment, 2024)

A personalized regression model for predicting thermal sensation based on local skin temperature in moderate summer conditions - Yun Qi; Rui Wang; Chaoyi Zhao; Chao Ding; Chenqiu Du; Jiazheng Zhang; Xuan Zhang; Xinchang Chen; Mingjie Zhang; Qingfeng Bie; Meng Ge (Energy and Buildings, 2023)

Development of electrospun fish gelatin film containing lauroyl arginate ethyl and its application in large yellow croaker (Pseudosciaena crocea) preservation - Qingfeng Dong; Lan Yang; Leiwen Xiang; Yueliang Zhao; Li Li (Food Control, 2023)

Coupling of soil methane emissions at different depths under typical coastal wetland vegetation types - Kun Li; Zihao Wang; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xiaoyan Shen; Xiaoya Xu; Qingfeng Chen (Chemosphere, 2023)

Quercetin inhibits the NOX2/ROS-mediated NF-κB/TXNIP signaling pathway to ameliorate pyroptosis of cardiomyocytes to relieve sepsis-induced cardiomyopathy - Hao Zhao; Xin Lin; Qingfeng Chen; Xiaoyue Wang; Yongya Wu; Xiaoxia Zhao (Toxicology and Applied Pharmacology, 2023)

Boosting hydrogen evolution on MoS2 via synergistic regulation of interlayer dislocations and interlayer spacing - Longlu Wang; Feiran Zhang; Ning Sun; Lingbin Xie; Ting Zhi; Qingfeng Zhang; Zhongzhong Luo; Xia Liu; Shujuan Liu; Qiang Zhao (Chemical Engineering Journal, 2023)

Comparison of spatiotemporal burial and contamination of heavy metals in core sediments of two plateau lakes with contrasting environments: implication for anthropogenic-driven processes - Xiaolei Wang; Qingfeng Jiang; Zihan Zhao; Ximou Han; Jinliang Liu; Qun Liu; Bin Xue; Hao Yang (Environmental Monitoring and Assessment, 2023)

Interannual variation in gross ecosystem production and evapotranspiration in a temperate semiarid grassland undergoing vegetation recovery - Xinhao Li; Tianshan Zha; Peng Liu; Charles P.-A. Bourque; Xin Jia; Yun Tian; Chuan Jin; Xiaoshuai Wei; Xinyue Liu; Hongxian Zhao; Qingfeng Xu; Shaorong Hao (Agricultural and Forest Meteorology, 2023)

Millennial-scale changes in the Asian monsoon during the MIS12 period as recorded by a Chinese stalagmite - Shaohua Yang; Shitao Chen; Yongjin Wang; Qingfeng Shao; Liangcheng Tan; Zhenqiu Zhang; Kan Zhao; Zhenjun Wang; Yijia Liang; Xiumin Zhai; Chuan-Chou Shen; R. Lawrence Edwards (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Pyrite and sulfur-coupled autotrophic denitrification system for efficient nitrate and phosphate removal - Xuzhen Liu; Changsheng Zhao; Tongtong Xu; Wei Liu; Qingfeng Chen; Luzhen Li; Yu Tan; Xiaokai Wang; Yanan Dong (Bioresource Technology, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Short-term Dietary Selenium Deficiency Induced Liver Fibrosis by Inhibiting the Akt/mTOR Signaling Pathway in Rats - Lichun Qiao; Xue Lin; Yan Zhao; Qingfeng Wang; Haobiao Liu; Mei You; Qian Yuan; Zhihao Yang; Wenming Bian; Jiaxin Liu; Ziwei Guo; Jing Han (Biological Trace Element Research, 2023)

Variation in Sunshine Duration and Related Aerosol Influences at Shangdianzi GAW Station, China: 1958–2021 - Weijun Quan; Zhiqiang Ma; Ziming Li; Xiaolan Li; Yingruo Li; Xiangao Xia; Huaigang Zhou; Hujia Zhao; Zhenfa Wang; Weiwei Pu; Fan Dong; Di He; et al. (Journal of Meteorological Research, 2023)

Graphene nano zinc oxide reduces the expression and release of antibiotic resistance-related genes and virulence factors in animal manure - Haibo Zhang; Weikun Guan; Jun Shu; Sen Yu; Yingmin Xiong; Gao Liu; Yuhong Zhong; Jia Chen; Zhigang Zhao; Ning He; Qingfeng Xing; Dongsheng Guo; et al. (Science of The Total Environment, 2023)

Effects of load-related parameters on the dynamic response of concrete-filled double-skin steel tube K-joints under lateral impact loading - Qingfeng Yan; Jigang Zhang; Zhehao Ma; Feifei Liu; Guoliang Zhao; Chi Gu; Hanyu Song; Weicheng Zhang (Ocean Engineering, 2023)

Stalagmite multi-proxy records of weak Asian summer monsoon interval during Termination III as an analogue to Termination I - Gongzhe Chen; Shitao Chen; Shan Zhang; Zhenjun Wang; Qingfeng Shao; Xianfeng Wang; Zhenqiu Zhang; Kan Zhao; Yongjin Wang (Quaternary Science Reviews, 2023)

Soil nitrogen content and key functional microorganisms influence the response of wetland anaerobic oxidation of methane to trivalent iron input - Zihao Wang; Kun Li; Feifei Yan; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xinyi Xu; Ying Zhang; Xiaoyan Shen; et al. (Chemosphere, 2023)

Methamphetamine induces cardiomyopathy through GATA4/NF-κB/SASP axis-mediated cellular senescence - Xu Zhao; Jiancong Lu; Cui Zhang; Chuanxiang Chen; Manting Zhang; Jingyi Zhang; Qingfeng Du; Huijun Wang (Toxicology and Applied Pharmacology, 2023)

Middle Pleistocene Pongo from Ganxian Cave in southern China with implications for understanding dental size evolution in orangutans - Hua Liang; Terry Harrison; Qingfeng Shao; Jean-Jacques Bahain; Jianxin Zhao; Christopher J. Bae; Wei Liao; Wei Wang (Journal of Human Evolution, 2023)

Characteristics and health risk assessment of heavy metal pollution in atmospheric particulate matter in different regions of the Yellow River Delta in China - Ting Liu; Changsheng Zhao; Qingfeng Chen; Luzhen Li; Guorui Si; Lei Li; Beibei Guo (Environmental Geochemistry and Health, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Phenological responses of Bactrocera dorsalis (Hendel) to climate warming in China based on long-term historical data - Pumo Cai; Yunzhe Song; Litao Meng; Jia Lin; Mengting Zhao; Qingfeng Wu; Chuanpeng Nie; Yanyan Li; Qinge Ji (International Journal of Tropical Insect Science, 2023)
It is well accepted that the phenology of insects whose life activities are closely related to temperature is changing in response to global climate warming. To investigate the impacts of climate warming on the phenology of Bactrocera dorsalis (Hendel) across large temporal and spatial scales, this study collected historical data on the occurrence and population dynamic of this pest in China, and systematically explored its phenological responses. The results showed a delayed trend for the dates of first occurrence, end occurrence, population initial growth, and population peak of B. dorsalis in China during 40 years, and the changes of the latter two phenological parameters were significant. The mean temperature in spring and summer were the key climatic factors affecting the occurrence and population growth of B. dorsalis in China, respectively. Moreover, the B. dorsalis data in eastern, southern, central, and southwestern China showed spatial heterogeneity of phenological responses to climate warming at a regional scale. B. dorsalis phenology and their changing patterns with climate warming varied by geographical location. This study provides valuable information for future monitoring, prediction, and prevention of the oriental fruit fly in the context of climate warming.

Carbonate cementing minerals in rhizoliths from Badain Jaran Desert: Implication for pedo-diagenesis and environment of dune soil - Qingfeng Sun; Kazem Zamanian; Arnaud Huguet; Guido L.B. Wiesenberg; Tianlei Zhao; Ziqiang Lei (Rhizosphere, 2023)

Effect of Maillard reaction conditions on the gelation and thermal stability of whey protein isolate/d-tagatose conjugates - Yao Meng; Xiao Zhao; Yunqing Jiang; Qingfeng Ban; Xibo Wang (Food Chemistry, 2023)

In-situ activities of anaerobic bacteria and methanogenic archaea in shallow lakes over the Anthropocene: A case study of Lake Wuliangsu - Yuxin He; Qingfeng Zhao; Dayang Sun; Huanye Wang (Chemical Geology, 2023)

Experimental and numerical study on the dynamic behavior of concrete-filled double steel tubular T-joint under impact loading - Qingfeng Yan; Jigang Zhang; Feifei Liu; Zhehao Ma; Guoliang Zhao; Chi Gu; Hanyu Song; Yang Zhao (Ocean Engineering, 2023)

Preparation of N-doped cellulose-based hydrothermal carbon using a two-step hydrothermal induction assembly method for the efficient removal of Cr(VI) from wastewater - Xinkun Zhao; Hongxu Liang; Zihao Wang; Daijia Li; Xiaoyan Shen; Xiaoya Xu; Kun Li; Qingyue Xiang; Yihan Wu; Qingfeng Chen (Environmental Research, 2023)

Soil nitrogen substances and denitrifying communities regulate the anaerobic oxidation of methane in wetlands of Yellow River Delta, China - Zihao Wang; Kun Li; Xiaoyan Shen; Feifei Yan; Xinkun Zhao; Yu Xin; Linhui Ji; Qingyue Xiang; Xinyi Xu; Daijia Li; Junhao Ran; Xiaoya Xu; et al. (Science of The Total Environment, 2023)

Sulfonate-modified calixarene-based porous organic polymers for electrostatic enhancement and efficient rapid removal of cationic dyes in water - Lechen Tian; Shiyuan Zhou; Jiaojiao Zhao; Qingfeng Xu; Najun Li; Dongyun Chen; Hua Li; Jinghui He; Jianmei Lu (Journal of Hazardous Materials, 2023)

Ice-volume and insolation influences on hydroclimate changes in central eastern China during the antepenultimate glacial period - Quan Wang; Shayue Yuan; Yijia Liang; Kan Zhao; Qingfeng Shao; Zhenqiu Zhang; Junji Zhu; Xinggong Kong; Yongjin Wang; Jianghu Lan; Hai Cheng; Chengwei Xia; et al. (Science China Earth Sciences, 2023)

Long-term effects of cattle manure application on the soil aggregate stability of salt-affected soil on the Songnen Plain of North-Eastern China - Shuo Zhao; Fei Yu; Cheyu Zhai; Rui Zhong; Ying Zhao; Yong Wang; Juan Zhang; Qingfeng Meng (Journal of Soils and Sediments, 2023)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Dual-channel recycling e-waste pricing decision under the impact of recyclers’ loss aversion and consumers’ bargaining power - Zhen Li; Jia Zhao; Qingfeng Meng (Environment, Development and Sustainability, 2022)

Development of suspension culture technology and hormone effects on anthocyanin biosynthesis for red Cyclocarya paliurus cells - Yuan Liu; Qi Liang; Daobang Tang; Yuqin Chen; Jianwei Zang; Wenjia Zhao; Jiguang Chen; Qingfeng Zhang; Zhongping Yin (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Holocene hydroclimate changes on the north‐eastern Tibetan Plateau inferred from geochemical records in Lake Gyaring - Dongliang Ning; Qingfeng Jiang; Ming Ji; Yuchen Xu; Xiang Kuai; Ying Ge; Wenwei Zhao (Journal of Quaternary Science, 2022)
The north‐eastern Tibetan Plateau (TP) is an ideal region for understanding the interaction between the Asian Summer Monsoon (ASM) and the Westerlies. Here we present a high‐resolution elemental record from Lake Gyaring in the source region of the Yellow River to investigate the paleo‐hydroclimate changes over the past ~10 ka. Our results show that lithogenic elements (Ti, Rb, Mn, Ti, Zn and Ni) increased while carbonate‐related elements (Ca, Sr and Mg) decreased up the core sediments, indicating that the effective moisture on the north‐eastern TP has steadily increased throughout the Holocene. This inference is also supported by the gradual augmentation and diminution of Rb/Sr and Ca/(Ti + Fe + Al) ratios, respectively. The persistent wetting trend on the north‐eastern TP inferred from our study disagrees with the Holocene pattern of the ASM but corresponds well with that of the Westerlies. This implies that the strengthening Westerlies since the Holocene might have played a more important role than monsoon circulation in controlling the hydroclimate changes on the north‐eastern TP. However, the significant increase in the mid‐Holocene might be related to the combined effects of the strengthened ASM and Westerlies. Ultimately, Northern Hemisphere solar insolation and the substantial remnant of ice sheets might have controlled Holocene moisture availability on the north‐eastern TP through their influence on the intensity of the Westerlies and ASM as well as Atlantic Ocean sea surface temperatures.

Late Jurassic adakitic ore-bearing granodiorite porphyry intrusions in the Xiaokele porphyry Cu (–Mo) deposit, Northeast China: implications for petrogenesis and tectonic setting - Yonggang Sun; Bile Li; Zhonghai Zhao; Qingfeng Ding; Fanbo Meng; Xusheng Chen; Ye Qian; Yujin Li (Acta Geochimica, 2021)

Design, synthesis and biological evaluation of Schiff’s base derivatives as multifunctional agents for the treatment of Alzheimer’s disease - Jian Shi; Yi Zhou; Keren Wang; Qinge Ma; Rongrui Wei; Qingfeng Li; Yiyang Zhao; Zhanpin Qiao; Shuang Liu; Yumin Leng; Wenmin Liu; Zhipei Sang (Medicinal Chemistry Research, 2021)

GelMA combined with sustained release of HUVECs derived exosomes for promoting cutaneous wound healing and facilitating skin regeneration - Danyang Zhao; Zhencheng Yu; Yun Li; Yu Wang; Qingfeng Li; Dong Han (Journal of Molecular Histology, 2020)

Assessing impacts of climate change on habitat suitability of Coregonus ussuriensis and other coldwater fishes in northern China - Baoxiu Xing; He Chen; Qingfeng Chen; Yan Zhang; Zifang Liu; Zhao Yang (Environmental Science and Pollution Research, 2019)

Different pollutant removal efficiencies of artificial aquatic plants in black-odor rivers - Qingfeng Chen; Zhao Yang; Kemei Qi; Changsheng Zhao (Environmental Science and Pollution Research, 2019)

Runoff and sediment variation and attribution over 60 years in typical Loess Plateau basins - Qiaoqiao Zhao; Li Wang; Hao Liu; Qingfeng Zhang (Journal of Soils and Sediments, 2019)

The expansion process of a Stellera chamaejasme population in a degraded alpine meadow of Northwest China - Fuyuan Gao; Kaiming Li; Chengzhang Zhao; Heng Ren; Xiaoying Nie; Dongyu Jia; Linfeng Li; Qingfeng Li (Environmental Science and Pollution Research, 2019)

Overexpression of VaWRKY12, a transcription factor from Vitis amurensis with increased nuclear localization under low temperature, enhances cold tolerance of plants - Langlang Zhang; Tingting Zhao; Xiaoming Sun; Yi Wang; Chang Du; Zhenfei Zhu; Duncan Kiragu Gichuki; Qingfeng Wang; Shaohua Li; Haiping Xin (Plant Molecular Biology, 2019)

L-3-n-Butylphthalide reduces ischemic stroke injury and increases M2 microglial polarization - Fangfang Li; Qingfeng Ma; Haiping Zhao; Rongliang Wang; Zhen Tao; Zhibin Fan; Sijia Zhang; Guangwen Li; Yumin Luo (Metabolic Brain Disease, 2018)

The chimeric genes in the hybrid lineage of Carassius auratus cuvieri (♀)×Carassius auratus red var. (♂) - Qingfeng Liu; Yanhua Qi; Qiuli Liang; Xiujuan Xu; Fangzhou Hu; Jing Wang; Jun Xiao; Shi Wang; Wuhui Li; Min Tao; Qinbo Qin; Rurong Zhao; et al. (Science China Life Sciences, 2018)

Geochemistry of pyrite and chalcopyrite from an active black smoker in 49.6°E Southwest Indian Ridge - Bo Yuan; Yaomin Yang; Hongjun Yu; Yuexia Zhao; Qingfeng Ding; Jichao Yang; Xin Tang (Marine Geophysical Research, 2018)

Overexpression of VaWRKY14 increases drought tolerance in Arabidopsis by modulating the expression of stress-related genes - Langlang Zhang; Jun Cheng; Xiaoming Sun; Tingting Zhao; Mingjun Li; Qingfeng Wang; Shaohua Li; Haiping Xin (Plant Cell Reports, 2018)

Risk assessment of flood disaster and forewarning model at different spatial-temporal scales - Jun Zhao; Juliang Jin; Jinchao Xu; Qizhong Guo; Qingfeng Hang; Yaqian Chen (Theoretical and Applied Climatology, 2018)

Structure-based design, synthesis, PPAR-γ activation, and molecular docking of N-substituted phthalimides - Bin Xiao; Shumin Wang; Zhanfei She; Qingfeng Cao; Na Zhao; Xiangrong Tian; Yixin Su (Medicinal Chemistry Research, 2017)

Water Resources Risk Assessment Model based on the Subjective and Objective Combination Weighting Methods - Jun Zhao; Juliang Jin; Jiezhong Zhu; Jinchao Xu; Qingfeng Hang; Yaqian Chen; Donghao Han (Water Resources Management, 2016)

Down-regulation of FBP1 by ZEB1-mediated repression confers to growth and invasion in lung cancer cells - Juan Zhang; Jiangtao Wang; Hui Xing; Qingfeng Li; Qianfeng Zhao; Jing Li (Molecular and Cellular Biochemistry, 2016)

Distribution of carbon and nitrogen in water-stable aggregates and soil stability under long-term manure application in solonetzic soils of the Songnen plain, northeast China - Qingfeng Meng; Yuting Sun; Jing Zhao; Lianren Zhou; Xianfa Ma; Meng Zhou; Wei Gao; Guangcheng Wang (Journal of Soils and Sediments, 2014)

Atrazine biodegradation by Arthrobacter strain DAT1: effect of glucose supplementation and change of the soil microbial community - Shuguang Xie; Rui Wan; Zhao Wang; Qingfeng Wang (Environmental Science and Pollution Research, 2013)

Nitrogen impacts on atrazine-degrading Arthrobacter strain and bacterial community structure in soil microcosms - Xiaode Zhou; Qingfeng Wang; Zhao Wang; Shuguang Xie (Environmental Science and Pollution Research, 2013)

Hepatic stellate cells produce vascular endothelial growth factor via phospho-p44/42 mitogen–activated protein kinase/cyclooxygenase-2 pathway - Yi Zhao; Yanqing Wang; Qiang Wang; Zhengrong Liu; Qingfeng Liu; Xin Deng (Molecular and Cellular Biochemistry, 2012)

A comparison of different optimization algorithms for retrieving aerosol optical depths from satellite data: an example of using a dual-angle algorithm - Xihan Mu; Qingfeng Shen; Zhao-Liang Li; Guangjian Yan; José Antonio Sobrino (International Journal of Remote Sensing, 2011)